β-Adrenergic receptor stimulation causes cardiac hypertrophy via a Gβγ/Erk-dependent pathway - Vidal, Marie; Wieland, Thomas (Cardiovascular research, 2012)
AbstractAims. Activation of the β1-adrenergic receptor and its G protein, Gs, induces cardiac hypertrophy. However, activation of classic Gαs effectors, adenyl
Online publish-ahead-of-print 27 July 2012
Gesehen am 11.10.2018